Mathematics Achievement - Intelligence Quotient (IQ): A Study of Simple Relations in Class 10 High School Students - Hendriyanto, Agus; Juandi, Dadang (Universitas Sebelas Maret, 2022)
This study aims to test whether students' mathematics achievement affects their Intelligence Quotient levels based on the correlation and regression. The sample of the study consisted of 81 new students from one Madrasah Aliyah in Surakarta City. The learning achievement data and IQ data were obtained from school documents. This study used a quantitative approach with a survey design. Data were analyzed using descriptive statistical analysis and inferential statistics covering prerequisite tests in the form of normality tests and linearity tests, classical assumption tests in the form of multicollinearity tests and heteroscedasticity tests, and hypothesis tests in the form of simple regression analysis. The results showed that the mean score of students' mathematics achievement was 45.78 with the smallest score of 8 and the highest score of 92. While the mean score of student's IQ was 112.43 with the lowest score of 100 and the highest score of 126. The test results showed that students' mathematics achievement affected their IQ level with the regression equation of Y=107.739+0.103X indicating that for every 1% addition of math achievement scores, the IQ score will increase by 0.103. Therefore, it can be said that when students' mathematics achievement increases, their IQ will also increase. The influence of students' mathematics achievement on IQ is 16% with a correlation value of 0.4.